Ambient air pollution and prostate cancer risk in a population-based Canadian case-control study. Issue 4 (19th August 2022) - Youogo, Leslie Michele-Ange Kouam; Parent, Marie-Elise; Hystad, Perry; Villeneuve, Paul J.
Abstract : Background: Ambient air pollution is a human carcinogen and a possible risk factor for prostate cancer. Methods: We investigated associations between ambient concentrations particulate matter 2.5 (PM2.5 ) and nitrogen dioxide (NO2 ) and incident prostate cancer in a Canadian case-control study. Between 1994 and 1997, cases were identified from provincial cancer registries, and a population-based series of controls was recruited. Among men 50 years of age or older, risk factor and residential history data (1975 to 1994) were collected from 1, 420 prostate cancer cases and 1, 424 controls. Three methods were used to estimate the residential mean exposure to PM2.5 and NO2 during this period: (1) satellite-derived observations; (2) satellite-derived observations scaled with historical fixed-site measurements; and (3) a national land-use regression (LUR) model. Odds ratios (ORs) and their 95% confidence intervals (CIs) in relation to interquartile range (IQR) increases in PM2.5 and NO2 were estimated using logistic regression, adjusting for personal and contextual factors. Results: We found positive associations between exposure to PM2.5 and NO2 over the previous 20 years and prostate cancer. An IQR increase in PM2.5 (3.56 µg/m 3 for satellite and 4.48 µg/m 3 for scaled satellite observations) yielded ORs of 1.28 (95% CI = 1.07, 1.52) and 1.20 (95% CI = 1.03, 1.40), respectively. For NO2, IQR increases (1.45 ppb for satellite, 15.18 ppb for scaled satellite-derived information, and 15.39 ppb for the national LUR) were associated with ORs of 1.09 (95% CI = 0.95, 1.24), 1.21 (95% CI = 1.02, 1.43), and 1.19 (95% CI = 1.03, 1.38), respectively. Conclusions: Our findings support the hypothesis that ambient air pollution increases the risk of prostate cancer.